Prevalence and Risk Factors of Hernia in Patients With Rectus Abdominis Diastasis: A 10-Year Multicenter Retrospective Study - Yuan, Sue; Wang, Honghong; Zhou, Jie (Frontiers in Surgery, 2021)
Objectives: Hernias are very common in patients with rectus abdominis diastasis (RAD). This study aimed to identify and compare the risk factors and patterns of hernia between men and women with RAD. Method: We included patients with RAD from six hospitals within the Partners Healthcare System in Massachusetts, USA between 2009 and 2018. Univariate and multivariable binary logistic regression analyses were used to identify risk factors associated with hernia. Results: Of the 1,294 RAD cases, 866 (67%) were women. The risk of RAD in women was 1.9 times greater than that of men. There were 240 men (56.1%) and 310 women (35.8%) having one or more hernia (P < 0.001). Of the 550 hernia cases, 278 men and 175 women had umbilical hernia (28.1 vs. 38.3%, P = 0.085). The distribution of hernia type differed between the two groups (P < 0.0001). Multivariate analysis identified that alcohol use [odd ratio (OR) 1.74 (1.17–2.59); P = 0.006] and depressive disorder [OR 1.90 (1.209–2.998); P = 0.005] were risk factors of coexisting hernia for men with RAD; age [OR 1.51 (1.33–1.72); P = 0.000] and smoking/tobacco use [OR 1.66 (1.13–2.44); P = 0.010] were risk factors of hernia for women. Conclusion: The prevalence and risk factors of hernia in women with RAD significantly differed from that in men with RAD. Umbilical hernia is an important type of hernia. Alcohol use and depressive disorder in men, and age and smoking in women were risk factors of hernias in patients with RAD.